Structural, Morphological and Interfacial Investigation of H2V3O8 upon Mg2+ Intercalation. Issue 4 (14th February 2023) - Surace, Yuri; Romio, Martina; Amores, Marco; Hamid, Raad; Cupid, Damian; Sauer, Markus; Foelske, Annette; Jahn, Marcus
Abstract: Magnesium‐ion batteries (MIBs) are a promising alternative to lithium‐ion batteries due to their higher theoretical energy densities and lower cost. However, fundamental limitations such as the sluggish diffusion of Mg 2+ ions into cathode materials have hindered their practical implementation. In this work, the structural, morphological and interfacial changes of H2 V3 O8, a promising cathode material for MIBs, are elucidated upon Mg 2+ intercalation in TFSI‐based electrolytes. Post‐mortem analysis revealed a shrinkage of the interlayer distance, an increase in cell volume, and a decrease of the surface V 5+ /V 4+ ratio during discharge. These changes were only partially reversible upon subsequent charge due to Mg trapping. A cathode electrolyte interphase (CEI) formed mainly of TFSI − anions, its decomposition products, and MgF2 was detected on the surface of H2 V3 O8 . The CEI thickness and chemical composition vary upon charge and discharge as well as during prolonged cycling, and its presence correlates with the additional capacity recorded during discharge. Our study aims to contribute to a better understanding of Mg 2+ intercalation and cathode‐electrolyte interaction in high voltage cathode materials for MIBs. Abstract : Mg 2+ intercalation in H2 V3 O8 : Post‐mortem analysis at different charge and discharge states and selected cycle numbers of H2 V3 O8, a promising cathode material for Mg‐ion batteries, reveals partially reversible changes in the crystal structure upon Mg 2+ intercalation, evidence of Mg trapping and formation of a cathode electrolyte interface containing TFSI ions and MgF2 .